Detection and remediation of mercury contaminated environment by nanotechnology: Progress and challenges. (15th January 2022) - Liu, Yonghua; Chen, Hanqing; Zhu, Nali; Zhang, Jing; Li, Yufeng; Xu, Diandou; Gao, Yuxi; Zhao, Jiating
Abstract: Hg pollution is a global concern due to its high ecotoxicity and health risk to human beings. A comprehensive understanding of the fast-developed technology applied in determining and controlling Hg pollution is beneficial for risk assessment and field remediation. Herein, we mainly assembled the recent progress on Hg treatment in the environment by nanotechnology. The advantages and disadvantages of the conventional and nanotechnology-based methods commonly used in water-/soil-Hg remediation were compared and summarized. Specifically, green nanomaterials derived from plant tissues (e.g., nanocellulose) have prominent merits in remediation of Hg contaminated environments, including high efficiency in Hg removal, low cost, environment-friendly, and easily degradable. Based on the theories of Hg biogeochemistry and existed researches, four promising pathways are proposed, 1) developing surface-modified green nanocellulose with high selectivity and affinity towards Hg; 2) designing effective dispersants in preventing nanocellulose from agglomeration in soil; 3) mediating soil properties by adding green nanomaterials-based fertilizers; 4) improving plant-Hg-extract capacity with green nanomaterials addition. Briefly, more efficient and available approaches are still expected to be developed and implemented in the natural environment for Hg remediation.